"Together we stand." : the experiences of peacekeepers social functioning under the UNIFIL crisis management operation - Mäntymaa, Sanna-Maria (2019)
Social functioning is considered one of the key areas of analysis when discussing the overall performance of a peacekeeper. Other important areas are physical-, psychological- and ethical performance. This study focuses on the concept of social functioning and considers its different definitions and their meaning. Social functioning has not been widely studied in the area of peacekeeping operations and is therefore an interesting area to study closer.